ЖАС ӨСПИРИМЛЕР МИНЕЗ-ҚУЛҚЫНДАҒЫ БАЗЫ БИР МАШҚАЛАЛАР - Қадрекова, А.Қ.; Сабирова, М. (FAN va JAMIYAT, 2018)
The article is devoted to the reasons of negative behavior of children, the measures of solving this problem, the educational role of a family and influence of environment on the solution of this issue.